Pengaruh senam otak terhadap fungsi kognitif lansia demensia - Inabah, Siti Nasywa; Isnaeni, Yuli; Salmiyati, Suri (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Dementia in the elderly is a health problem that is increasing as the elderly population grows. The prevalence of dementia in Indonesian elderly aged 65 years and older reaches 27.9%, while in those aged 60 years and older, the prevalence ranges from 20-33%. Dementia causes cognitive decline in memory, thinking, concentration, and orientation, which impacts the independence of the elderly. Purpose: To determine the effect of brain exercise on cognitive function in elderly with dementia. Method: This study used a True Experimental Design with a Pretest–Posttest Control Group Design. The study population was all elderly with dementia at the Suka Sehat Yogyakarta Community Health Post (Posyandu). A sample of 20 respondents was selected using total sampling. Respondents were divided into intervention and control groups. Data analysis was performed using the Wilcoxon Signed Rank Test and the Mann–Whitney test with α = 0.05. Results: The Wilcoxon test showed a significant improvement in cognitive function in the intervention group after brain exercise (p = 0.007). The control group showed a significant decline in cognitive function (p = 0.007). The Mann-Whitney test showed a significant difference in cognitive function between the two groups (p = 0.000). Conclusion: Brain gymnastics significantly improved cognitive function in elderly people with dementia.   Keywords: Brain Gym; Cognitive Function; Dementia; Older Adults.   Pendahuluan: Demensia pada lansia merupakan masalah kesehatan yang meningkat seiring pertambahan jumlah penduduk lanjut usia. Prevalensi demensia pada lansia di Indonesia yang berusia ≥65 tahun mencapai 27.9%, sedangkan pada usia ≥60 tahun berkisar antara 20-33%. Demensia menyebabkan penurunan fungsi kognitif berupa gangguan daya ingat, kemampuan berpikir, konsentrasi, dan orientasi yang berdampak pada penurunan kemandirian lansia. Tujuan: Untuk mengetahui pengaruh senam otak terhadap fungsi kognitif pada lansia dengan demensia. Metode: Penelitian ini menggunakan desain True Experimental Design dengan metode Pretest–Posttest Control Group Design. Populasi penelitian adalah seluruh lansia dengan demensia di Posyandu Suka Sehat Yogyakarta. Sampel berjumlah 20 responden yang dipilih menggunakan teknik total sampling. Responden dibagi menjadi kelompok intervensi dan kelompok kontrol. Analisis data dilakukan menggunakan uji Wilcoxon Signed Rank Test dan uji Mann–Whitney dengan α = 0.05. Hasil: Uji Wilcoxon menunjukkan peningkatan fungsi kognitif yang signifikan pada kelompok intervensi setelah diberikan senam otak (p = 0.007). Kelompok kontrol menunjukkan terjadi penurunan fungsi kognitif yang signifikan (p = 0.007). Uji Mann Whitney menunjukkan perbedaan fungsi kognitif yang bermakna antara kedua kelompok (p = 0.000). Simpulan: Senam otak berpengaruh signifikan terhadap peningkatan fungsi kognitif pada lansia dengan demensia.   Kata Kunci: Demensia; Fungsi Kognitif; Lansia; Senam Otak.